GENITALIC STUDIES ON FOUR INDIAN SPECIES OF GENUS SPILARCTIA BUTLER (ARCTIIDAE : LEPIDOPTERA) - S. KIRTI, JAGBIR; SINGH`, AMRIT PAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Male and female genitalia of four Indian Species of genus Spillarctia Butler have been studied. These characters have been included in the revised characterization of the genus.